KERAPATAN DAN VIABILITAS KONIDIA BEAUVERIA BASSIANA DAN METARHIZIUM ANISOPLIAE PADA MEDIA IN VITRO PH RENDAH - Rizkie, Lilian; Herlinda, Siti; ., Suwandi; Irsan, Chandra; ., Susilawati; Lakitan, Benyamin (Universitas Lampung, 2017)
Conidial density and viability of Beauveria bassiana and Metarhizium anisopliae grown on the low-pH in vitro medium. Liquid bioinsecticide with active ingredient from conidial entomopathogenic fungus has major constraints, namely short shelf life due to declining conidial viability and density is caused by low pH in the bioinsecticide carrier. This experiment aimed to measure the loss of conidial viability and density of Beauveria bassiana and Metarhizium anisopliae isolates grown on in vitro medium with low pH. Entomopathogenic fungus isolates were used as much as 28 isolates grown on in vitro medium at low pH, namely pH 5, 4, 3, and 2. The results showed that the fungus isolate that had the highest conidial density on in vitro medium at pH 5 was found on isolates of B. bassiana with code BPcMs (2.583 x 109 conidia mL-1), while the lowest one was found on isolates of B. bassiana with code of BWS Pantura (0.825x109 conidia mL-1). All isolate conidial density from in vitro medium with pH 2 decreased regularly. Conidial density of BPcMs isolate decreased to 2.483 x 109conidia mL-1, as well as BWS Pantura isolate also decreased to 0.425x109 conidia mL-1. The highest conidial viability at pH 5 was found on isolates of B. bassiana with code of BPcMs (51.572%), while the lowest conidial viability was found on isolate of B. bassiana with BTmPc code (15.040%). At pH 2, almost isolates tested had low conidial viability. The conidial viability of isolates BPcMs decreased to 47.037%%, while the isolates BTmPc also decreased to 12.778%. Therefore, the lower of the pH of the in vitro medium was, the lower of conidial viability and density of B. bassiana and M. anisopliae was